ANALYSIS OF THE CLINICAL COURSE OF TRAUMATIC KNEE JOINT INJURIES IN PATIENTS WITH COMORBIDITIES - Boskina, M.G. (Актуальні проблеми сучасної медицини Вісник Української медичної стоматологічної академії, 2025)
Objective: To investigate the diagnostic characteristics and clinical course of traumatic knee injuries in patients with various types of comorbid pathology and to develop a pathophysiologically justified approach to their classification. Materials and Methods: A prospective cohort study was conducted involving 126 patients with traumatic knee injuries who underwent arthroscopic treatment from January 2020 to February 2025. Patients were divided into three groups based on pathophysiological principles: individuals having no metabolic disorders (n=57, 45.2%), individuals having metabolic disorders without vascular complications (n=42, 33.3%), and individuals having both metabolic and vascular disorders (n=27, 21.5%). Clinical manifestations, laboratory parameters, functional status using the Knee Injury and Osteoarthritis Outcome Score and Visual Analogue Scale were assessed before surgery and on the 3rd, 7th, and 12th days after intervention, along with arthroscopic findings. Results: The groups classified according to pathophysiological principles demonstrated significant differences in inflammatory marker levels, clinical course, and postoperative recovery. The highest level of inflammatory markers at admission was observed in patients with metabolic and vascular disorders (median C-reactive protein 22.5 mg/L [interquartile range: 17.8-27.3]), while the lowest was in patients without comorbid pathology (7.8 mg/L [interquartile range: 5.2-10.4]). Severe synovitis was detected in 33.3% of patients in group III, 11.9% of patients in group II, and only 5.3% of patients in group I (p<0.001). A statistically significant correlation was established between comorbid status and the degree of synovitis (Spearman's correlation coefficient=0.61, p<0.001). The diagnostic value of both standard clinical examination methods and magnetic resonance imaging declined with increasing levels of comorbidity: specifically, the sensitivity of functional tests decreased from 86.3% in patients without comorbidities to 63.0% in those with high comorbidity. Functional recovery was also slower in patients with comorbid conditions: by the 12th postoperative day, the overall Knee Injury and Osteoarthritis Outcome Score (KOOS) averaged 61.4 points in group I, 56.3 points in group II, and only 49.1 points in group III (p < 0.001). Conclusions: A pathophysiological approach to classifying patients with traumatic knee injuries is clinically justified and facilitates optimization of the diagnostic process. Comorbid status has a significant impact on the diagnostic accuracy of standard examination methods, the severity of inflammation, and the rate of postoperative recovery. Taking into account the pathophysiological characteristics of different patient groups allows for more accurate prediction of inflammatory and reparative processes as well as supports the selection of patient-tailored management strategies.